SOME REGULARITIES OF THE DISTRIBUTION OF THE CONTENT OF FREE RADICALS AND VANADIUM (IV) IN OIL BY GEOLOGICAL SECTIONS OF THE EMBA REGION DEPOSITS - G.A.Artur; E. Mussin; А.S. Kalauova; А.А Nazhetova; R.N. Nasirov (Academic Scientific Journal of Chemistry, 2019)
In laboratory practice, is proposed a method for determining vanadium (IV) and free radicals (FR) in crude oils by electron paramagnetic resonance (EPR) at liquid nitrogen temperature. An important scientific and practical result of the proposed method for the determination of vanadium in crude oils, in contrast to the method of American authors is low nitrogen consumption, and an additional advantage of the method lies in the low cost of the process, since it eliminates the use of expensive temperature attachments for mass laboratory determinations of vanadium. In scientific work, this method was applied to determine vanadium and FR from the section of the Emba region’s oil fields. It has been established that with increasing depth and age of oil-bearing rocks, the density of oil decreases, as well as the content of tetravalent vanadium and FR in it. In some fields of the Emba oil-bearing region (North Kotyrtas, Kara-Arna), is noted an inverse pattern - an increase in the density of oil, the concentration of vanadium and FR is observed during the transition from an elevated part of the formation to a lower part.